2019
DOI: 10.1016/j.heliyon.2019.e02114
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of chronic liver disease among young/middle-aged adults in Northern Italy: role of hepatitis B and hepatitis C virus infection by age, sex, ethnicity

Abstract: Background Sparse population-based data are available on the prevalence and etiology of chronic liver disease (CLD) in Italy. The study aims to assess the role of hepatitis B virus (HBV) and hepatitis C virus (HCV) infection in CLD according to age, gender and ethnicity. Methods Clinically diagnosed CLD in the general population aged 20–59 years in the Veneto Region (North-Eastern Italy) were identified through the Adjusted Clinical Groups System, by record linkage of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 29 publications
4
11
0
Order By: Relevance
“…The highest prevalence of CLD was found in the age group of 41-60 years of age. This is consistent with the study conducted by Fedeli U et al, which indicated that the prevalence of CLD among males increased with age until 50-54 years (Fedeli et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…The highest prevalence of CLD was found in the age group of 41-60 years of age. This is consistent with the study conducted by Fedeli U et al, which indicated that the prevalence of CLD among males increased with age until 50-54 years (Fedeli et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…Other studies in African countries have identified a comparable major pattern of HBV infection among CLD patients: (57.7%) in Ethiopia [18] and (58.0%) in Nigeria [12]. A greater proportion of the patients (21.7%) had HCV as the cause of their CLD which was similar to the (22.5%) obtained in Ethiopia [19], however very low compared to the (43.1%) in Italy [4]. The geographical variations may have contributed to this findings, which implies that the prevalence of HCV infection among individuals with CLD is higher in Europe compared to Africa.…”
Section: Distribution and Determinants Of Etiologies Of Chronic Liversupporting
confidence: 66%
“…Globally, the distribution of CLDs comprises non-alcoholic fatty liver diseases [NALD] (60%), hepatitis B viral infection [HBV] (29%), hepatitis C viral infection [HCV] (9%), and alcoholic liver diseases [ALD] (2%) [3]. However, depending on the geographical prevalence of etiologies (hepatitis viruses, alcohol consumption, and metabolic syndrome), a large degree of geographical variation exist in the pattern of CLDs [4]. For instance, viral hepatitis is prevalent in Africa, Asia and Latin America, whereas ALD and NALD is predominant in Western countries [2].…”
Section: Introductionmentioning
confidence: 99%
“…The study was done in the Department of Biochemistry, Teerthanker Mahaveer College & Research Center General Medicine OPD in Moradabad, Uttar Pradesh from January 2021 to December 2021. A total of 100 subjects under the age limit 20-60 years [18] were selected and categorized into two classes. 50 diagnosed cases of chronic liver disease (alcoholic liver disease, non-alcoholic fatty liver disease, liver cirrhosis, chronic viral hepatitis) recruited for this study, were included in class I, while, class II included 50 apparently healthy individuals age and sex matched.…”
Section: Methodsmentioning
confidence: 99%